1993
DOI: 10.1093/ajcn/58.5.622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a gastric delivery system for iron supplementation in pregnancy

Abstract: The present investigation was undertaken to assess the efficacy of oral iron supplementation during pregnancy by using a gastric delivery system (GDS). Three hundred seventy-six pregnant women between 16 and 35 y of age and 14 and 22 wk gestation were selected if mild anemia was present (hemoglobin concentration 80-110 g/L). The participants were randomly assigned to one of three study groups given no iron, two FeSO4 tablets (100 mg Fe) daily, or one GDS capsule (50 mg Fe) daily. Blood was obtained initially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
5

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 8 publications
0
29
0
5
Order By: Relevance
“…A estratégia utilizada pelo serviço de saúde para sanar a deficiência de ferro é a suplementação medicamentosa com sais de ferro, devido ao seu baixo custo e boa absorção (EKSTRÖM et al 1996;SIMMONS et al 1993).…”
Section: Methodsunclassified
“…A estratégia utilizada pelo serviço de saúde para sanar a deficiência de ferro é a suplementação medicamentosa com sais de ferro, devido ao seu baixo custo e boa absorção (EKSTRÖM et al 1996;SIMMONS et al 1993).…”
Section: Methodsunclassified
“…At present it is almost an established fact that iron supplementation improves maternal iron status. It is reported that iron supplements increase hemoglobin, serum ferritin, mean cell volume, serum iron, and transferrin saturation [16][17][18][19][20][21][22][23] . But the result of our study seems controversial in terms of established facts, as a large proportion of anemic pregnant women were, in fact, taking iron supplementation provided by GoN for free (table 2).…”
Section: Anemia and Iron Deficiencymentioning
confidence: 99%
“…Although iron-deficiency anemia during pregnancy is associated with preterm delivery and delivering a low-birthweight baby (38 ), well designed, randomized control trials are needed to evaluate the effectiveness of universal iron supplementation on mitigating adverse birth outcomes. Some studies have indicated that adequate iron supplementation during pregnancy reduces the prevalence of irondeficiency anemia (6,10,(39)(40)(41)(42)66,104 ), but over the last few decades, the recommendation by the Council on Foods and Nutrition and other groups to supplement iron intake during pregnancy has not resulted in a reduced prevalence of anemia among low-income, pregnant women (4,9,105 ). Evidence on iron supplement use is limited, however, so it is not known how well the recommendation has been followed.…”
Section: Primary Preventionmentioning
confidence: 99%